To solve this system, you could do the following steps:%0D%0A%0D%0A3x+4y=48%0D%0A3%0D%0A%0D%0A+%0D%0A4%0D%0A%0D%0A=%0D%0A48%0D%0A %0D%0A6x+2y=60%0D%0A6%0D%0A%0D%0A+%0D%0A2%0D%0A%0D%0A=%0D%0A60 To solve this system, you could do the following steps:%0D%0A%0D%0A3x+4y=48%0D%0A3%0D%0A%0D%0A+%0D%0A4%0D%0A%0D%0A=%0D%0A48%0D%0A %0D%0A6x+2y=60%0D%0A6%0D%0A%0D%0A+%0D%0A2%0D%0A%0D%0A=%0D%0A60

1 answer

To solve this system of equations:
1. Start with the first equation, 3x+4y=48.
2. Multiply the coefficient of x, 3, by the entire second equation, 6x+2y=60. This gives us 18x+6y=180.
3. Multiply the coefficient of y, 4, by the entire second equation, 6x+2y=60. This gives us 24x+8y=240.
4. Subtract the equation from step 2 from the equation from step 3. This gives us 6x+2y=60.
5. Now we have a system of two equations: 6x+2y=60 and 3x+4y=48.
6. Multiply the first equation by -2 to eliminate the y term. This gives us -12x-4y=-120.
7. Add the equation from step 6 to the second equation. This gives us -9x=-72.
8. Solve for x by dividing both sides of the equation by -9. x = 8.
9. Substitute the value of x back into one of the original equations to solve for y. Using the first equation, when x = 8, 3(8) + 4y = 48. This simplifies to 24 + 4y = 48.
10. Subtract 24 from both sides of the equation to isolate the y term. This gives us 4y = 24.
11. Divide both sides of the equation by 4 to solve for y. y = 6.

The solution to the system of equations is x = 8 and y = 6.